The Study of Investigational Profile of Common Pesticide Poisoning Cases admitted at SAIMS, Indore - Waghmare, Chandra Shekhar; Nigam, Manish; Mishra, Pradeep K; Patel , Shailendra (Journal of Indian Academy of Forensic Medicine, 2014)
A prospective study was done in Shri Aurobindo Medical College Hospital, Indore during 1st January 2012 to 20th August 2013. 110 cases were admitted with history of pesticide poisoning during this period, out of them 10 cases were excluded, as they left the hospital within 1-2 hours of hospitalization. Most common poison was Organophosphorus (46 cases). Rodenticides 14 cases, Aluminium Phosphide 12 cases, Ethylene Di bromide 5 cases, others 3 cases and unknown poison was consumed by 2 peoples. Investigations like Liver function test, renal function test and electrolytes were studied in common pesticide poison i.e. Organophosphorus, Aluminium Phosphide and ethylene Di bromide. Liver function test was raised in most of the cases of ethylene Di bromide poisoning. Renal Function Test (RFT) was normal in most of the cases of Organophosphorus and Aluminium Phosphide and EDB poisoning. Sodium, Potassium and Chloride showed normal levels in most of the poisoning.